Unprotected Left-Main Coronary Angioplasty in the Elderly in a High Volume Catheterization Centre without On-Site Surgery Facilities: Immediate and Medium Term Outcome—The Old-Placet Registry. (23rd February 2015) - Gagnor, A.; Tomassini, F.; Cerrato, E.; Rolfo, C.; Gambino, A.; Giolitto, S.; Favro, E.; Bollati, M.; Tizzani, E.; Varbella, F.
Abstract : We aim to assess clinical feasibility and efficacy of unprotected left main (ULM) percutaneous coronary intervention (PCI) in patients older than 75 years over a 6-year period and with 2-year follow-up demonstrating that PCI is a feasible revascularization strategy even in absence of on-site cardiothoracic support. Nevertheless, the outcome of these high-risk patients is still hampered by a sensible in-hospital mortality rate. Older patients have a higher mortality at follow-up (10.0 versus 0.8%, P = 0.014), while younger patients have a low mortality after the acute phase (15.7 versus 8.4%, P = 0.15).